Recurrent advanced rectal malignant melanoma that discontinued anti‐PD‐1 antibody after complete response and was refractory to rechallenge. Issue 1 (25th June 2022) - Saito, Shintaro; Yasuda, Masahito; Araki, Takeshi; Ida, Azusa; Kuriyama, Yuko; Uehara, Akihito; Kishi, Chikako; Endo, Yukie; Ogawa, Hiroomi; Motegi, Sei‐ichiro
Abstract : We report a case of 70‐year‐old woman with rectal malignant melanoma that recurred in the pelvic lymph node one year after surgery. Nivolumab was initiated and she achieved complete response after one year, but she discontinued nivolumab at her instance. At a follow‐up 21 months after the discontinuation of nivolumab, a pelvic lymph node metastasis recurrence and a lung metastasis discovered. Nivolumab rechallenge was initiated, but it was not successful.